Rząd Jędrzeja Moraczewskiego 17 XI 1918-16 I 1919 r. (struktura, funkcjonowanie, dekrety) - Golcon, Jacek (Przegląd Nauk Historycznych, 2009)
Jędrzej Moraczewski's Cabinet was the first government to maintain control of such a significant part of Poland (the entire Kingdom of Poland together with western Galicia); however, from the very beginning it had to struggle with a truly dramatic economic situation in the Polish territory. In the middle of 1919 war damages were estimated to reach about 14 billion francs! The government began its activity in the times of growing social radicalism; yet, the process of the state structure formation proceeded efficiently, mainly due to the existing machinery of the former Regency Council. The cabinet successfully withstood the chaos, which had been spreading in the country in the first weeks of independence, as well as prevented Bolshevik revolution, for which Polish communists had been striving. This success resulted from a balanced policy of the government, which admitted to power neither the Right nor the communist Left, and which won the favour of the leftist electorate, i.e. working classes. At the same time the government assurred social rights and thus provided bearable living conditions (other factors - the fact of regaining independence, resulting in social enthusiasm along with the external threat, significantly strengthening the bond between the government and the nation, were greatly important). But not everyone in the society could appreciate the significance of the government's social reforms. Without doubt, it was caused by incomprehension of such far-reaching reforms in many circles, as well as by political and ideological animosities between different parties. This process was additionally intensified by district particularism. Also unfavourable attitude towards new authorities demonstrated by the western countries could have exerted negative influence on the government's picture in the eyes of the Polish society. The great western powers still considered the Polish National Committee, residing in Paris, as the Polish "government in exile". Nonetheless, by applying the accomplishec-facts strategy, the Cabinet of Moraczewski managed to implement revolutionary changes and efficiently avoided disturbances in the society. In comparison to the situation from the times of partitions this was one of the greatest achievements of his government.